The determinants of the Choice between Green and Conventional Buildings in the Gauteng Office market - Phillips, Leandre (Graduate School of Business (GSB), 2019)
The purpose of this study is to identify the key factors which drive investment in or occupancy of green buildings by landlords and tenants and to identify the benefits they derive over traditional buildings. In order to assess the significance of certain factors such as rental, hypothesis tests were conducted with logistic regressions and verified by interviews. Three hypothesis were tested two of which looked at the rentals and operational cost for each type of building , these revealed that the medians as well as distributions of each showed no significant differences between the two type buildings. The last hypothesis test various other factors for any significance between the buildings and no significant findings were found. The importance of sustainability is increasingly being emphasized across industries and more so the property industry given their contribution to greenhouse gas emissions. Green buildings were developed to address these consequences. As such it is important to know the financial returns realized in property portfolio to support the case of green buildings in emerging markets.